Recidivism Among Justice-Involved Youth: Findings From JJ-TRIALS. (September 2020) - Robertson, Angela A.; Fang, Zhou; Weiland, Doris; Joe, George; Gardner, Sheena; Dembo, Richard; Mcreynolds, Larkin; Dickson, Megan; Pankow, Jennifer; Dennis, Michael; Elkington, Katherine
Recidivism, and the factors related to it, remains a highly significant concern among juvenile justice researchers, practitioners, and policy makers. Recent studies highlight the need to examine multiple measures of recidivism as well as conduct multilevel analyses of this phenomenon. Using data collected in a National Institute on Drug Abuse (NIDA)-funded Juvenile Justice-Translational Research on Interventions for Adolescents in the Legal System (JJ-TRIALS) cooperative agreement, we examined individual- and site-level factors related to 1-year recidivism among probation youth in 20 sites in five states to answer research questions related to how recidivism rates differ across sites and the relationships between individual-level variables and a county-level concentrated disadvantage measure and recidivism. Our findings of large site differences in recidivism rates, and complex relationships between individual and county-level predictors of recidivism, highlight the need for more nuanced, contextually informed, multilevel approaches in studying recidivism among juveniles.